New Insights into Mortality-Related Risk Factors in Infective Endocarditis: Results from the Brandenburg State Endocarditis Register - Ostovar, Roya; Schroeter, Filip; Seifi Zinab, Frarzane; Fritzsche, Dirk; Minden, Hans-Heinrich; Lasheen, Nirmeen; Hartrumpf, Martin; Ritter, Oliver; Dörr, Gesine; Albes, Johannes Maximilian (The Thoracic and Cardiovascular Surgeon, 2024)
Objective Endocarditis as a potentially life-threatening disease with high complication and mortality rates. In recent years, an increase in the incident of endocarditis has been reported throughout Europe. In the aging society, successful treatment is complex and challenging owing to the high rate of multimorbidity.Methods We initiated a statewide prospective multicenter endocarditis registry in 2020. Perioperative risk factors, comorbidities, microbiological, laboratory and imaging diagnostics, complications, and mortality including 1-year follow-up were collected. The present midterm analysis includes factors influencing mortality in the first 313 patients.Result In-hospital mortality and 1-year mortality were 28.4 and 40.9%, respectively. Preoperative risk factors include age (p < 0.001), EuroSCORE II (p < 0.001), coronary artery disease (p = 0.022), pacemaker probe infection (p = 0.033), preoperative left ventricular ejection fraction (LVEF), systemic inflammatory response syndrome (SIRS), pulmonary edema, heart failure, septic emboli, acute renal failure, impaired coagulation, hypalbuminemia (p < 0.001), and N-terminal prohormone of brain natriuretic peptide (NTproBNP) (p = 0.001). The presence of peri-annular abscess, perforation, and shunt were associated with increased mortality (p = 0.004, 0.001, and 0.004, respectively). In addition, cardiopulmonary bypass time influenced mortality (p = 0.002). The main postoperative causes of death were multi-organ failure, renal failure, vasoplegia, and low-output syndrome (p < 0.001). Previous endocarditis was 7.7%, while 35.5% were prosthetic valve recipients and 33.6% were redo surgeries.Conclusion Our first registry data show the complexity of endocarditis patients and the challenging treatment. Some risk factors can be treated preoperatively. For instance, hypalbuminemia and the duration of the procedure can be controlled with adequate albumin substitution and carefully planned procedures restricted to the essential requirements, that is, hybrid approaches with consecutive interventions.
Keywords: endocarditis; outcomes (includes mortality morbidity); heart valve surgery; inflammation systemic (including cells mediators); surgery; complications